Functional characterizations of trace spaces in Lipschitz domains - Touhami, Soumia (2019)
Using a factorization theorem of Douglas, we prove functional characterizations of trace spaces Hs (∂Ω) involving a family of positive selfadjoint operators. Our method is based on the use of a suitable operator by taking the trace on the boundary ∂Ω of a bounded Lipschitz domain Ω ⊂ R d and applying Moore–Penrose pseudoinverse properties together with a special inner product on H1 (Ω). We also establish generalized results of the Moore– Penrose pseudoinverse.